Algorithm of Development and Methodology of Using Software for Information Conversion in the Educational Process - Gerasimov, V. A.; Boyprav, O. V. (Cifrovaâ transformaciâ (Online), 2023)
The article is devoted to the results of substantiation and creation of the algorithm for the development of a software tool for information transformation, which is advisable to be used in the process of digital transformation of education in higher educational institutions. In the course of substantiating this algorithm, the role of studying issues related to the information transformation in the formation of professional competencies of future specialists in the field of information technology is determined; the advantages of using the C language in comparison with other programming languages for software development are determined; the possibilities of working with memory using pointers in the C programming language are considered. The key code fragments of a software tool developed in accordance with the proposed algorithm related to the transformation of textual information into numeric data and numeric data into textual information are presented. Examples of the operation of this soft-ware tool are demonstrated and the ways for its use is presented when conducting laboratory or practical work in disciplines whose topics are related to information technology, with students of the 1st and 2nd years of study. The ways of improving the proposed algorithm aimed at increasing the number of academic disciplines, within which it is advisable to use the software developed in accordance with it, are determined.